THE ROLE OF MICROFERTILIZERS IN IMPROVING SEED QUALITY RAPHANUS SATIVUM D. SEEDS. VAR. OLEIFERA METRG. IN THE CARPATHIAN REGION OF UKRAINE - Hlyva, Valentyna; Oleksandra Petrivna, Voloshchuk; Ihor Stepanovuch, Voloshchuk; Valentyna Viktorivna, Hlyva; Halyna Yaroslavivna , Bilovus; Khrystyna Vasylivna , Bilonizhka (Journal of Agricultural Sciences (Belgrade), 2025)
The purpose of the research was to determine the effect of foliar fertilizing with microfertilizers on the formation of elements of varietal productivity and indicators of sowing qualities of oil radish seeds. The objects of research were the Zhuravka and Fakel varieties. The methodological basis consisted of general scientific and special research methods (field method). The area of the registration plot was 50 m2, the placement of varieties was sequential with three repetitions. The research was conducted during 2021-2023 on the basis of the department of seed production and seed science of the Institute of Agriculture of the Carpathian region of the National Academy of Agrarian Sciences, located in the Carpathian region of Ukraine. Growing seeds of high quality oilseed radish as one of the important green manure crops is an urgent task for expanding sown areas in the region. Only by producing a sufficient amount of seed material, especially new, more productive varieties and effective agricultural cultivation measures, can the desired results be achieved. A small number of scientific publications are devoted to this issue, which requires further scientific justification. The experiment compared four options for using microfertilizers on leaves against the background of mineral nutrition - N30P60K70 + N50 BBCН 14–16 (leaf development) + N20 BBCН 52–53 (inflorescence appearance). The results presented in the article emphasize the effectiveness of using microfertilizers: Oracle multicomplex, Yara Vita Rexolin, Intermag-oliiny. It was established that under their influence, seed yield increased by 0.38–0.46 t ha-1, the weight of 1000 seeds – 1.17–2.15 g, germination energy – 2.2–3.8%, laboratory germination – 2.4-4.2%. The research results can be used by agricultural enterprises and farms to adjust the nutrition system through the main application of mineral fertilizers and additional microfertilizers in foliar feeding of plants, which ensures a more complete realization of the genetic potential of oilseed radish and ensures high sowing qualities of grown seeds.
Keywords: oilseed radish, HTC, weight of 1000 seeds, germination energy, laboratory germination